Comprehensive geriatric assessment in the older cancer patient: coming of age in clinical cancer care. (December 2014) - Owusu, Cynthia; Berger, Nathan A
Cancer care at the extremes of life, in the young and the old, is characterized by unique issues associated with pediatrics and geriatric medicine, accentuated by the special vulnerabilities of these groups. In response to these needs, the field of pediatric oncology has been well honed to deal with the special problems associated with juvenile cancer patients. While most adult oncologists consider themselves well prepared to deal with older cancer patients, the current expansion of the geriatric population – their variable levels of fitness, frailty and vulnerability, the fact that cancer is primarily a disease of older adults, the significant expansion of agents and approaches to treat cancer, as well as their resultant toxicities and complications – has led to the development of specialized geriatric oncologists. Moreover, the special characteristics and needs of these patients have led to the evolution of new guidelines for evaluation, management and the conduct of research in older patients with cancer.